Artificial neural networks for machining processes surface roughness modeling - Pontes, Fabricio J.; Ferreira, Joao R.; Silva, Messias B. [UNESP]; Paiva, Anderson P.; Balestrassi, Pedro Paulo (Springer London Ltd, 2010)
In recent years, several papers on machining processes have focused on the use of artificial neural networks for modeling surface roughness. Even in such a specific niche of engineering literature, the papers differ considerably in terms of how they define network architectures and validate results, as well as in their training algorithms, error measures, and the like. Furthermore, a perusal of the individual papers leaves a researcher without a clear, sweeping view of what the field's cutting edge is. Hence, this work reviews a number of these papers, providing a summary and analysis of the findings. Based on recommendations made by scholars of neurocomputing and statistics, the review includes a set of comparison criteria as well as assesses how the research findings were validated. This work also identifies trends in the literature and highlights their main differences. Ultimately, this work points to underexplored issues for future research and shows ways to improve how the results are validated.
Keywords: Artificial neural networks; Machining; Surface roughness; Modeling